Statehood and governance: challenges in Sub-Saharan Africa - Stephan Klingebiel; Sven Grimm (Deutsches Institut für Entwicklungspolitik (DIE), 2007)
Sub-Saharan Africa comprises 48 states at various stages of social, economic and political development. Despite the heterogeneity of these countries, the following general developments relating to statehood and governance in the past 15 years can at least be identified: Such pan-African initiatives as the New Partnership for Africa's Development (NEPAD) and the African Union (AU) have done away with the political taboo of interference in internal affairs; it is no longer an accepted justification for inaction. Since the early 1990s processes of political transformation have begun in many sub-Saharan African countries; regime change has occurred in many cases. Notwithstanding regression in Zimbabwe and Ethiopia, for example, Africa as a whole has become politically more open; the participation of the people in political processes through elections has increased. Political transformation has tended to have little effect effect on the accountability of regimes; many political systems continue to be characterized by neopatrimonialism. The policies and service delivery undertaken by African countries have been inadequate. This is true both of basic social and economic services and of governance in the security sphere. In many cases, state does not have a secure monopoly of power. Although there have been changes for the better, major governance deficits persist in almost all parts of the continent and require additional efforts by the African countries themselves. The expected economic results of improved governance are a long time coming for many citizens; in the long term this poses a threat to the stability of the continent. The scale of external support in the form of development aid has a major influence on the political structures and policy-making of the countries assisted. In many cases, governance structures are being weakened by external actors.
Keywords: 330